Analysis of Patients with Central Nervous System Infection at Our Clinic: Five-year Results - Balin, Safak Ozer; Sagmak Tartar, Ayse; Demirdag, Kutbeddin; Akbulut, Ayhan (Galenos Publ House, 2019)
Introduction: This study aimed to determine the epidemiological data, clinical and laboratory findings, morbidity, and mortality of patients with central nervous system infection (CNSI). Materials and Methods: Patients who were followed-up in our clinic with a diagnosis of CNSI between 2013 and 2018 were reviewed retrospectively. Results: A total of 55 patients with a mean age of 46 +/- 19 (19-90) years were included in the study; 58.1% of the patients were male. Acute bacterial meningitis was observed in 54.5% of the patients, aseptic meningitis in 23.6%, tuberculous meningitis in 5.5%, and meningoencephalitis in 16.4% (88.8% of these patients were defined as highly probable encephalitis). The most common symptom was fever. The prevalence of the classical triad (fever, neck stiffness, and change in mental status) in patients with acute bacterial meningitis was 36.6%. Streptococcus pneumoniae was the most common causative agent identified in cerebrospinal fluid (CSF) and blood culture. Cerebrospinal fluid acid-fast bacillus positivity in tuberculous meningitis and CSF herpes simplex virus polymerase chain reaction-1 positivity in meningoencephalitis was 33.3% The complication rate was 18.1%. The only mortality was in one patient with acute bacterial meningitis. Conclusion: According to the results of our study, fever, change in mental status, headache, and signs of meningeal irritation are essential in predicting CNSI. However, these indicators rarely presented altogether in our patients. Therefore, patients who do not exhibit the classical triad but are suspected of CNSI should undergo lumbar puncture for CSF analysis and antimicrobial treatment should be started as soon as possible. The low mortality rate among our patients once again demonstrates the importance of this approach.
Kliniğimizde Yatan Santral Sinir Sistemi Enfeksiyonu Tanılı Hastaların Analizi: Beş Yıllık Sonuçlar
Keywords: Acyclovir; ceftriaxone; epidemiology; encephalitis; vancomycin